Strategi Komunikasi Interpersonal Guru dalam Membangun Engagement dan Regulasi Emosi Siswa di Sekolah Dasar - K.Theresia Laksmi Savitri; Putu Suwid nyana; Ida Bagus Putrayasa; I Wayan Rasna; I Nengah Suandi (Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to analyze interpersonal communication strategies employed by teachers and their contribution to student engagement and emotional regulation at Sekolah Dasar Katolik Karya Singaraja. The research employs a qualitative descriptive approach to explore how verbal, nonverbal, empathic, affirmative, corrective, and persuasive communication are implemented in classroom interactions. The findings indicate that interpersonal communication plays a significant role in fostering meaningful learning interactions and supporting students’ cognitive, social, and emotional development. Verbal and persuasive communication function as scaffolding that facilitates understanding and active participation, while nonverbal communication strengthens message delivery and classroom interaction dynamics. Empathic and affirmative communication contribute to creating a psychologically safe learning environment that enhances students’ confidence and intrinsic motivation. Meanwhile, corrective communication serves as constructive feedback that guides students in improving their learning performance. These findings align with Vygotsky’s social constructivism theory, Rogers’ humanistic theory, and Hattie and Timperley’s feedback theory, which emphasize the importance of social interaction, emotional support, and effective feedback in the learning process. Overall, interpersonal communication strategies implemented by teachers are not merely instructional tools but also pedagogical approaches that foster holistic student development.